Expression of children’s rights at school: pupils’ opinion - Malinauskienė, Daiva; Klungevičiūtė, Gintarė (Social Welfare: Interdisciplinary Approach, 2015)
The article analyses 6-7 graders’ opinion about expression of children’s rights at school. The study has revealed that the right to education, the right to be health, the right to healthy and safe environment are viewed by 6-7 graders as the most important. These rights are of particular significance for teenagers’ education, comprehensive development and socialization. The least important right to the teenagers is the right to participate in activities of the educational institution. The study has shown that most of pupils still believe that their rights are violated at school often or even always. Pupils lack emotional and physical security when at school. Among other causes, children’s insecurity may also be related to school community members’ occasional non-compliance with duties, as has been noted by pupils
Keywords: children’s rights; school; pupils